The Immigration Crime and Policy: Implementation of PPNS Authorities on Investigation - Syahrin, Muhammad Alvi (Universitas Negeri Semarang, 2018)
Immigration crime and criminal law are one of the interesting studies not only seen in terms of law enforcement but also criminal law politics and authority arrangements in immigration. For Indonesia, the problem of immigration is a challenging problem, not because it is only the location of Indonesia that is vast and has many access points for immigrants, but also the authority between institutions. Article 105 of Law Number 6 Year 2011 on Immigration, states that the Immigration Civil Servant Investigator is authorized as an Immigration criminal investigator conducted in accordance with the provisions. The results of this study are: (1) enforcement of immigration law conducted one of them with the investigation of perpetrators of violations of the Immigration Act. The process of investigating the perpetrators of violation of Immigration Law is based on the provisions of the Criminal Procedure Code as lex generalis and Immigration Law as lex specialis. In this research, law enforcement has been carried out in order to participate in trading fake immigration/passport travel documents by providing unauthorized data or incorrect information to the Immigration officer to obtain travel documents of the Republic of Indonesia for himself, (2) in implementing immigration law enforcement function there are still obstacles faced Immigration Civil Servant Investigator include low knowledge, lack of operational fund, lack of public participation in reporting the existence of foreigner in their environment, weakness of coordination with other law apparatus and obstacle from law factors.